Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
import system_of_complexes.basic | |
/-! | |
# The normed snake dual lemma: weak and non-weak | |
This file proves the weak normed snake dual lemma and the normed snake dual lemma: they are the | |
statements `weak_normed_snake_dual` and `normed_snake_dual`, respectively. | |
The principal definitions of the concepts in this file appear in Section 4 of the blueprint. | |
The two main results prove `is_(weak_)bounded_exact` for certain `system_of_complexes`. The | |
Lean-definitions of these concepts appears in `system_of_complexes.basic`. | |
Intuitively, the two predicates assert a version of exactness for a complex whose overall shape is | |
an inequality of the form | |
```lean | |
∥res ? - (M.d ??) ?∥ ≤ const * ∥(M.d ?? ?∥ + ε. | |
``` | |
(Recall that `res` is a restriction among certain complexes, `M.d` stands for a differential, | |
`const` is a constant; the error `ε` is a non-negative real number. For the weak version, we | |
quantify over all `0 < ε ∈ ℝ`. For the non-weak version, we use `ε = 0`.) | |
More in detail, at the heart of the computation, is a proof of an inequality of the form | |
```lean | |
∥res m - (M.d (i - 1) i) y∥ ≤ K * (1 + K' * r₁ * r₂) * ∥(M.d i (i + 1)) m∥ + ε. | |
``` | |
In the weak normed snake dual lemma, for any choice of positive `0 < ε`, we should be able to fix | |
the parameters so that the inequality above is satisfied. In the normed snake dual lemma, we want | |
the inequality above with `ε = 0`. As you will see, the bulk of the proof of the normed snake dual | |
lemma recycles the proof of the weak version. | |
The proof involves several estimations: we broke these proofs into smaller partial inequalities, | |
for three reasons. First, it streamlines the formalization. Second, it helps Lean processing the | |
statements, reducing processing times. Third, it allows us to us a large part of the argument for | |
both `weak_normed_snake_dual` and `normed_snake_dual`. | |
# Remark | |
While following the proof, keep an eye out for how the factor `ρ = 1 + K' * r₁ * r₂` forms itself. | |
Once the factor `ρ` is formed, we can almost treat it as a new strictly positive variable. | |
-/ | |
universe variables u | |
noncomputable theory | |
open_locale nnreal | |
open category_theory opposite normed_add_group_hom system_of_complexes | |
variables {M N P : system_of_complexes.{u}} {f : M ⟶ N} {g : N ⟶ P} | |
/- I (DT) extracted this lemma to speed up the proof of `weak_normed_snake_dual`. -/ | |
lemma ε₁_le_ε {ε ε₁ : ℝ} (hε : 0 ≤ ε) (mK : ℝ≥0) (hε₁ : ε₁ = ε / 2 * (1 + mK)⁻¹) : | |
ε₁ ≤ ε := | |
by { rw [hε₁, div_eq_mul_inv, mul_assoc, ← mul_inv], | |
exact mul_le_of_le_one_right hε (inv_le_one $ nnreal.coe_le_coe.mpr $ | |
one_le_mul one_le_two $ le_add_of_nonneg_right mK.2) } | |
/-! | |
First, we break off the main term `∥res m - (M.d i' i) m₁∥` into a sum of two expressions: | |
* `∥(res (f m) : N c i) - N.d i' i (res n₁)∥`, and | |
* `∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥`. | |
-/ | |
lemma norm_sub_le_split {k' c c₁ : ℝ≥0} {i i' i'' : ℕ} | |
[hk' : fact (1 ≤ k')] [fc : fact (c ≤ c₁)] | |
(hfnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (M c i)), ∥(f.apply) x∥ = ∥x∥) | |
{n₁ : N (k' * c) i'} {n₂ : N c i''} {nnew₁ : N c i'} {m₁ : M c i'} {m : (M c₁ i)} | |
(hm₁ : f m₁ = res n₁ - ((N.d i'' i') n₂) - nnew₁) : | |
∥res m - (M.d i' i) m₁∥ ≤ | |
∥(res (f m) : N c i) - N.d i' i (res n₁)∥ + ∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥ := | |
calc ∥res m - (M.d i' i) m₁∥ | |
= ∥f (res m - (M.d i' i) m₁)∥ : (hfnorm _ _ _).symm | |
... = ∥res (f m) - (N.d i' i (res n₁) - N.d i' i ((N.d i'' i') n₂ + nnew₁))∥ : | |
by rw [hom_apply, _root_.map_sub, ←hom_apply, ←hom_apply, ←res_apply, | |
←d_apply, hm₁, sub_sub, _root_.map_sub] | |
... = ∥(res (f m) - N.d i' i (res n₁)) + N.d i' i ((N.d i'' i') n₂ + nnew₁)∥ : | |
by rw [sub_eq_add_neg, neg_sub, sub_eq_neg_add, ← add_assoc, ← sub_eq_add_neg] | |
... ≤ ∥res (f m) - N.d i' i (res n₁)∥ + ∥N.d i' i ((N.d i'' i') n₂ + nnew₁)∥ : norm_add_le _ _ | |
/-! | |
We then massage the left-hand side. The proof of this lemma is deceptively simple, since | |
there is a lot of typeclass work happening in the background. In particular, the `c` in the sea of | |
underscores of the second line is crucial for the *previous* line to compile. | |
(The hypothesis `(hN_adm : N.admissible)` is only used via `(hN_adm.res_norm_noninc _ c _ _ _)`, | |
producing the inequality | |
`(dis : ∥(res (res (f m) - (N.d i' i) n₁) : N c i)∥ ≤ ∥res (f m) - (N.d i' i) n₁∥)`.) | |
-/ | |
lemma norm_sub_le_mul_norm_add_lhs {k' K c c₁ : ℝ≥0} {ε₁ : ℝ} {i i' : ℕ} | |
[hk' : fact (1 ≤ k')] [fc₁ : fact (k' * c ≤ c₁)] [fc : fact (c ≤ c₁)] | |
{n₁ : N (k' * c) i'} {m : (M c₁ i)} | |
(hN_adm : N.admissible) | |
(hn₁ : ∥res (f m) - (N.d i' i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) : | |
∥(res (f m) : N c i) - N.d i' i (res n₁)∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁ := | |
calc ∥(res (f m) : N c i) - N.d i' i (res n₁)∥ | |
= ∥res (res (f m) - (N.d i' i) n₁)∥ : by rw [_root_.map_sub, d_res, ← res_res] | |
... ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁ : trans (hN_adm.res_norm_noninc _ c _ _ _) hn₁ | |
/-! | |
And we also massage the right-hand side. Here, the factor `K' * r₁ * r₂` appears. | |
(The hypothesis `(hN_adm : N.admissible)` is only used via `(hN_adm.d_norm_noninc _ _ i' i nnew₁)`, | |
producing the inequality `(dis : ∥(N.d i' i) nnew₁∥ ≤ ∥nnew₁∥)`.) | |
-/ | |
lemma norm_sub_le_mul_norm_add_rhs {k' K K' r₁ r₂ c c₁ : ℝ≥0} {ε₁ ε₂ : ℝ} | |
{i i' i'' : ℕ} (hii' : i' + 1 = i) | |
[hk' : fact (1 ≤ k')] [fc₁ : fact (k' * c ≤ c₁)] | |
(hgnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (N c i)), ∥g x∥ ≤ ↑r₁ * ∥x∥) | |
{n₁ : N (k' * c) i'} {n₂ : N c i''} {nnew₁ : N c i'} {m : (M c₁ i)} | |
(hN_adm : N.admissible) | |
(hn₁ : ∥res (f m) - (N.d i' i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) | |
(hp₂ : ∥res (g n₁) - (P.d i'' i') (g n₂)∥ ≤ K' * ∥(P.d i' (i' + 1)) (g n₁)∥ + ε₂) | |
(hnormnnew₁ : ∥nnew₁∥ ≤ r₂ * ∥g (res n₁ - ((N.d i'' i') n₂))∥) | |
(hfm : ∥g ((N.d i' i) n₁)∥ = ∥g (res (f m) - (N.d i' i) n₁)∥) : | |
∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥ ≤ | |
K * K' * r₁ * r₂ * ∥(N.d i (i+1)) (f m)∥ + K' * r₁ * r₂ * ε₁ + r₂ * ε₂ := | |
calc ∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥ | |
= ∥N.d i' i nnew₁∥ : by simp only [map_add, zero_add, d_d] | |
... ≤ r₂ * ∥g (res n₁ - (N.d i'' i') n₂)∥ : trans (hN_adm.d_norm_noninc _ _ i' i nnew₁) hnormnnew₁ | |
... = r₂ * ∥res (g n₁) - P.d i'' i' (g n₂)∥ : | |
by rw [hom_apply, _root_.map_sub, ←hom_apply, ←hom_apply, ←res_apply _ _ g, ←d_apply] | |
... ≤ r₂ * (K' * ∥P.d i' (i'+1) (g n₁)∥ + ε₂) : mul_le_mul_of_nonneg_left hp₂ r₂.coe_nonneg | |
... = r₂ * (K' * ∥g (res (f m) - N.d i' i n₁)∥ + ε₂) : by rw [d_apply _ _ g _, hii', hfm] | |
... ≤ r₂ * (K' * (r₁ * ∥res (f m) - N.d i' i n₁∥) + ε₂) : | |
mul_le_mul_of_nonneg_left (add_le_add_right (mul_le_mul_of_nonneg_left | |
(hgnorm _ _ _) K'.coe_nonneg) _) $ r₂.coe_nonneg | |
... = r₂ * (K' * r₁ * ∥res (f m) - N.d i' i n₁∥ + ε₂) : by rw mul_assoc | |
... ≤ r₂ * (K' * r₁ * (K * ∥(N.d i (i+1)) (f m)∥ + ε₁) + ε₂) : | |
mul_le_mul_of_nonneg_left (add_le_add_right (mul_le_mul_of_nonneg_left | |
hn₁ $ mul_nonneg K'.coe_nonneg r₁.coe_nonneg) _) r₂.coe_nonneg | |
... = _ : by ring | |
/-! | |
We collect the inequalities obtained so far: | |
* use `norm_sub_le_split` to split the norm into a sum of two terme; | |
* apply `norm_sub_le_mul_norm_add_lhs` to the left-hand-side; | |
* apply `norm_sub_le_mul_norm_add_rhs` to the right-hand-side. | |
The rest is simple manipulations of real numbers. | |
-/ | |
lemma norm_sub_le_mul_norm_add {k' K K' r₁ r₂ c c₁ : ℝ≥0} {ε ε₁ ε₂ : ℝ} | |
{i i' i'' : ℕ} (hii' : i' + 1 = i) | |
[hk' : fact (1 ≤ k')] [fc₁ : fact (k' * c ≤ c₁)] [fc : fact (c ≤ c₁)] | |
(hN_adm : N.admissible) | |
(hgnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (N c i)), ∥g x∥ ≤ ↑r₁ * ∥x∥) | |
(hfnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (M c i)), ∥(f.apply) x∥ = ∥x∥) | |
{n₁ : N (k' * c) i'} {n₂ : N c i''} {nnew₁ : N c i'} {m₁ : M c i'} {m : (M c₁ i)} | |
(hmulε₁ : ε₁ * (1 + K' * r₁ * r₂) = ε / 2) | |
(hle : (r₂ : ℝ) * ε₂ ≤ ε / 2) | |
(hn₁ : ∥res (f m) - (N.d i' i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) | |
(hp₂ : ∥res (g n₁) - (P.d i'' i') (g n₂)∥ ≤ K' * ∥(P.d i' (i' + 1)) (g n₁)∥ + ε₂) | |
(hnormnnew₁ : ∥nnew₁∥ ≤ r₂ * ∥g (res n₁ - ((N.d i'' i') n₂))∥) | |
(hm₁ : f m₁ = res n₁ - ((N.d i'' i') n₂) - nnew₁) | |
(hfm : ∥g ((N.d i' i) n₁)∥ = ∥g (res (f m) - (N.d i' i) n₁)∥) : | |
∥res m - (M.d i' i) m₁∥ ≤ (K + r₁ * r₂ * K * K') * ∥(M.d i (i + 1)) m∥ + ε := | |
calc | |
∥res m - (M.d i' i) m₁∥ ≤ ∥res (f m) - N.d i' i (res n₁)∥ + ∥N.d i' i ((N.d i'' i') n₂ + nnew₁)∥ : | |
norm_sub_le_split hfnorm hm₁ | |
... ≤ (K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) + | |
(K * K' * r₁ * r₂ * ∥(N.d i (i+1)) (f m)∥ + K' * r₁ * r₂ * ε₁ + r₂ * ε₂) : add_le_add | |
(norm_sub_le_mul_norm_add_lhs hN_adm hn₁) | |
(norm_sub_le_mul_norm_add_rhs hii' hgnorm hN_adm hn₁ hp₂ hnormnnew₁ hfm) | |
... = (K + r₁ * r₂ * K * K') * ∥N.d i (i+1) (f m)∥ + ε₁ * (1 + K' * r₁ * r₂) + r₂ * ε₂ : by ring | |
... = (K + r₁ * r₂ * K * K') * ∥N.d i (i+1) (f m)∥ + ε / 2 + r₂ * ε₂ : | |
congr_arg (λ e, (↑K + ↑r₁ * ↑r₂ * ↑K * ↑K') * ∥(N.d i (i + 1)) (f m)∥ + e + ↑r₂ * ε₂) hmulε₁ | |
... ≤ (K + r₁ * r₂ * K * K') * ∥N.d i (i+1) (f m)∥ + ε / 2 + ε / 2 : add_le_add_left hle _ | |
... = (K + r₁ * r₂ * K * K') * ∥(M.d i (i+1)) m∥ + ε : | |
by rw [add_assoc, add_halves', d_apply, hom_apply, hfnorm] | |
/-! | |
We shall apply this lemma with `ρ = K + r₁ * r₂ * K * K' = K * (1 + K' * r₁ * r₂)`. | |
-/ | |
lemma exists_norm_sub_le_mul_add {k k' c ρ : ℝ≥0} | |
{i : ℕ} | |
[hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] | |
(hM_adm : M.admissible) | |
(ex_le : (∀ (m : (M (k * (k' * c)) i)) (ε : ℝ), 0 < ε → | |
(∃ (i₀ : ℕ) (hi₀ : i₀ = i - 1) (y : (M c i₀)), | |
∥res m - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i (i + 1)) m∥ + ε))) | |
{m₁ : (M (k * k' * c) i)} | |
{ε : ℝ} (hε : 0 < ε) : | |
∃ (i₀ j : ℕ) (hi₀ : i₀ = i - 1) (hj : i + 1 = j) (y : (M c i₀)), | |
∥res m₁ - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i j) m₁∥ + ε := | |
begin | |
haveI : fact (k * (k' * c) ≤ k * k' * c) := { out := (mul_assoc _ _ _).symm.le }, | |
rcases ex_le (res m₁) ε hε with ⟨i₀, rfl, y, hy⟩, | |
rw [res_res, d_res] at hy, | |
refine ⟨i - 1, _, rfl, rfl, _⟩, | |
refine ⟨y, hy.trans (add_le_add_right (mul_le_mul_of_nonneg_left _ ρ.2) ε)⟩, | |
exact hM_adm.res_norm_noninc _ _ _ _ _, | |
end | |
/-! | |
This argument proves the main inequality in the case where the indices are `0` or `1`. | |
-/ | |
lemma norm_sub_le_mul_mul_norm_add {M N : system_of_complexes} {f : M ⟶ N} | |
{k k' K c : ℝ≥0} (mK : ℝ≥0) {ε ε₁ : ℝ} {m : M (k * (k' * c)) 0} {n₁ : N (k' * c) 0} {m₁ : M c 0} | |
(ee1 : ε₁ ≤ ε) | |
[hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] | |
(hfnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (M c i)), ∥(f.apply) x∥ = ∥x∥) | |
(inadm : ∥((res (res m : (M (k' * c) 0))) : (M c 0))∥ ≤ ∥(res m : (M (k' * c) 0))∥ ) | |
(hn₁ : ∥res (f m) - (N.d 0 0) n₁∥ ≤ ↑K * ∥(N.d 0 (0 + 1)) (f m)∥ + ε₁) : | |
∥res m - (M.d 0 0) m₁∥ ≤ (K * (1 + mK)) * ∥(M.d 0 (0 + 1)) m∥ + ε := | |
begin | |
simp only [d_self_apply, sub_zero, nnreal.coe_add, nnreal.coe_mul] at hn₁ ⊢, | |
rw [res_apply, hom_apply f (res m), hfnorm] at hn₁, | |
have new : fact (c ≤ k' * c) := { out := le_mul_of_one_le_left c.2 hk'.out }, | |
rw ←res_res _ _ _ new, | |
refine le_trans inadm (le_trans hn₁ _), | |
rw [d_apply, hom_apply f _, hfnorm], | |
refine add_le_add _ ee1, | |
rw mul_assoc, | |
refine (mul_le_mul_of_nonneg_left _ K.2), | |
exact le_mul_of_one_le_left (norm_nonneg _) (le_add_of_nonneg_right mK.2), | |
end | |
/-! | |
Note that `ε = 0` is allowed. Indeed, the weak normed snake dual lemma uses `0 ≤ ε`, while the | |
normed snake dual lemma uses `ε = 0`. | |
-/ | |
lemma exist_norm_sub_le_mul_norm_add {k k' K K' r₁ r₂ c₀ c : ℝ≥0} | |
{a i : ℕ} {ε : ℝ} (hε : 0 ≤ ε) | |
[hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] | |
(hN_adm : N.admissible) | |
(hgnrm : ∀ (c : ℝ≥0) (i : ℕ) (x : (N c i)), ∥g x∥ ≤ r₁ * ∥x∥) | |
(Hg : ∀ (c : ℝ≥0) [_inst_1 : fact (c₀ ≤ c)] (i : ℕ), | |
i ≤ a + 1 + 1 → ∀ (y : (P c i)), ∃ (x : (N c i)), g x = y ∧ ∥x∥ ≤ r₂ * ∥y∥) | |
(hg : ∀ (c : ℝ≥0) (i : ℕ), (range f.apply : add_subgroup (N c i)) = ker g.apply) | |
(hf : ∀ (c : ℝ≥0) (i : ℕ), (isometry (f.apply : M c i ⟶ N c i) : _)) | |
(hc : fact (c₀ ≤ c)) | |
(hi : i ≤ a) | |
{m : M (k * (k' * c)) i} {n₁ : N (k' * c) (i - 1)} | |
(hn₁ : ∥res (f m) - (N.d (i - 1) i) n₁∥ ≤ | |
K * ∥(N.d i (i + 1)) (f m)∥ + ε / 2 * (1 + K' * r₁ * r₂)⁻¹) | |
(Hi' : i - 1 ≤ a + 1) | |
(p₂ : P c (i - 1 - 1)) (hp₂ : ∥res (g n₁) - (P.d (i - 1 - 1) (i - 1)) p₂∥ ≤ | |
K' * ∥(P.d (i - 1) (i - 1 + 1)) (g n₁)∥ + ite (r₂ = 0) 1 (ε / 2 * (r₂)⁻¹)) : | |
∃ (i₀ : ℕ) (hi₀ : i₀ = i - 1) (y : (M c i₀)), | |
∥res m - (M.d i₀ i) y∥ ≤ (K + r₁ * r₂ * K * K') * ∥(M.d i (i + 1)) m∥ + ε := | |
begin | |
obtain ⟨n₂, rfl, hnormn₂⟩ := | |
Hg c (i - 1 - 1) (trans (nat.pred_le _) (trans Hi' (nat.le_succ _))) p₂, | |
let n₁' := N.d (i - 1 - 1) (i - 1) n₂, | |
obtain ⟨nnew₁, hnnew₁, hnrmnew₁⟩ := Hg c (i - 1) (trans Hi' a.succ.le_succ) (g (res n₁ - n₁')), | |
have hker : (res n₁ - n₁') - nnew₁ ∈ g.apply.ker, | |
{ rw [mem_ker, _root_.map_sub, sub_eq_zero, ←hom_apply, ←hom_apply, hnnew₁] }, | |
rw ←hg at hker, | |
obtain ⟨m₁, hm₁ : f m₁ = res n₁ - n₁' - nnew₁⟩ := (mem_range _ _).1 hker, | |
refine ⟨i - 1, rfl, m₁, _⟩, | |
have hfnrm : ∀ c i (x : M c i), ∥f.apply x∥ = ∥x∥ := λ c i x, (add_monoid_hom_class.isometry_iff_norm _).1 (hf c i) x, | |
by_cases hizero : i = 0, | |
{ subst hizero, | |
convert norm_sub_le_mul_mul_norm_add (K' * r₁ * r₂) _ hfnrm _ hn₁, | |
{ norm_cast, ring }, | |
{ exact ε₁_le_ε hε (K' * r₁ * r₂) rfl }, | |
{ exact (admissible_of_isometry hN_adm hf).res_norm_noninc _ _ _ _ _ } }, | |
{ refine norm_sub_le_mul_norm_add _ hN_adm hgnrm hfnrm _ _ hn₁ hp₂ hnrmnew₁ hm₁ _, | |
{ exact nat.succ_pred_eq_of_pos (nat.pos_of_ne_zero hizero) }, | |
{ rw inv_mul_cancel_right₀, | |
exact ne_of_gt (add_pos_of_pos_of_nonneg zero_lt_one (zero_le (K' * r₁ * r₂))) }, | |
{ by_cases H : r₂ = 0, | |
{ simp only [H, nnreal.coe_zero, if_true, zero_mul, (div_nonneg hε zero_le_two)] }, | |
{ simp only [H, nnreal.coe_eq_zero, if_false, mul_comm, | |
mul_inv_cancel_left₀ (nnreal.coe_ne_zero.mpr H)] } }, | |
{ have : f (res m : M (k' * c) i) ∈ f.apply.range, { rw mem_range, exact ⟨res m, rfl⟩ }, | |
rw [hg, mem_ker] at this, | |
rw [hom_apply g (res (f m) - (N.d (i - 1) i) n₁), res_apply, _root_.map_sub, this, | |
zero_sub, norm_neg, ←hom_apply] } } | |
end | |
/-! | |
We apply this lemma with `ρ = K + r₁ * r₂ * K * K'`. | |
-/ | |
lemma exists_norm_sub_le_mul {M : system_of_complexes} {k k' c ρ : ℝ≥0} | |
{i : ℕ} | |
[hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] | |
(hM_adm : M.admissible) | |
(ex_le : (∀ (m : (M (k * (k' * c)) i)), | |
(∃ (i₀ : ℕ) (hi₀ : i₀ = i - 1) (y : (M c i₀)), | |
∥res m - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i (i + 1)) m∥))) | |
(m₁ : (M (k * k' * c) i)) : | |
∃ (i₀ j : ℕ) (hi₀ : i₀ = i - 1) (hj : i + 1 = j) (y : (M c i₀)), | |
∥res m₁ - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i j) m₁∥ := | |
begin | |
haveI : fact (k * (k' * c) ≤ k * k' * c) := { out := (mul_assoc _ _ _).symm.le }, | |
rcases ex_le (res m₁) with ⟨i₀, rfl, y, hy⟩, | |
rw [res_res, d_res] at hy, | |
refine ⟨i - 1, _, rfl, rfl, _⟩, | |
refine ⟨y, hy.trans (mul_le_mul_of_nonneg_left _ ρ.2)⟩, | |
exact hM_adm.res_norm_noninc _ _ _ _ _, | |
end | |
variables (M N P f g) | |
/-! | |
Finally, we state and prove the weak normed snake dual lemma. | |
-/ | |
lemma weak_normed_snake_dual (k k' K K' r₁ r₂ : ℝ≥0) | |
[hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] | |
{a : ℕ} {c₀ : ℝ≥0} | |
(hN : N.is_weak_bounded_exact k K (a + 1) c₀) | |
(hP : P.is_weak_bounded_exact k' K' (a + 1) c₀) | |
(hN_adm : N.admissible) | |
(hgnrm : ∀ c i (x : N c i), ∥g x∥ ≤ r₁ * ∥x∥) | |
(Hg : ∀ (c : ℝ≥0) [fact (c₀ ≤ c)] (i : ℕ) (hi : i ≤ a + 1 + 1) (y : P c i), | |
∃ (x : N c i), g x = y ∧ ∥x∥ ≤ r₂ * ∥y∥) | |
(hg : ∀ c i, (f.apply : M c i ⟶ N c i).range = g.apply.ker) | |
(hf : ∀ c i, @isometry (M c i) (N c i) _ _ f.apply) : | |
M.is_weak_bounded_exact (k * k') (K + r₁ * r₂ * K * K') a c₀ := | |
begin | |
introsI c hc i hi, | |
apply exists_norm_sub_le_mul_add (admissible_of_isometry hN_adm hf), | |
intros m ε hε, | |
have hε₁ : 0 < ε / 2 * (1 + K' * r₁ * r₂)⁻¹ := mul_pos (half_pos hε) | |
(inv_pos.2 $ add_pos_of_pos_of_nonneg zero_lt_one ((K' * r₁ * r₂).coe_nonneg)), | |
obtain ⟨_, _, rfl, rfl, n₁, hn₁⟩ := | |
hN _ ⟨hc.out.trans $ le_mul_of_one_le_left' hk'.out⟩ _ (trans hi a.le_succ) (f m) _ hε₁, | |
have Hi' : i - 1 ≤ a + 1 := trans i.pred_le (trans hi a.le_succ), | |
obtain ⟨_, _, rfl, rfl, p₂, hp₂⟩ := hP _ hc _ Hi' (g n₁) | |
(if (r₂ : ℝ) = 0 then 1 else (ε / 2) * r₂⁻¹) _, | |
{ simp_rw [nnreal.coe_eq_zero r₂] at hp₂, | |
apply exist_norm_sub_le_mul_norm_add hε.le hN_adm hgnrm Hg hg hf hc hi hn₁ Hi' p₂, | |
convert hp₂, }, | |
{ by_cases H : r₂ = 0, | |
{ simp only [H, zero_lt_one, if_true, eq_self_iff_true, nnreal.coe_eq_zero] }, | |
{ simp only [H, nnreal.coe_eq_zero, if_false], | |
exact mul_pos (half_pos hε) (inv_pos.2 (nnreal.coe_pos.2 (zero_lt_iff.2 H))) } } | |
end | |
/-! | |
And also the normed snake dual lemma. | |
-/ | |
lemma normed_snake_dual {k k' K K' r₁ r₂ : ℝ≥0} | |
[hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] | |
{a : ℕ} {c₀ : ℝ≥0} | |
(hN : N.is_bounded_exact k K (a + 1) c₀) | |
(hP : P.is_bounded_exact k' K' (a + 1) c₀) | |
(hN_adm : N.admissible) | |
(hgnorm : ∀ c i (x : N c i), ∥g x∥ ≤ r₁ * ∥x∥) | |
(Hg : ∀ (c : ℝ≥0) [fact (c₀ ≤ c)] (i : ℕ) (hi : i ≤ a + 1 + 1) (y : P c i), | |
∃ (x : N c i), g x = y ∧ ∥x∥ ≤ r₂ * ∥y∥) | |
(hg : ∀ c i, (f.apply : M c i ⟶ N c i).range = g.apply.ker) | |
(hf : ∀ c i, @isometry (M c i) (N c i) _ _ f.apply) : | |
M.is_bounded_exact (k * k') (K + r₁ * r₂ * K * K') a c₀ := | |
begin | |
introsI c hc i hi, | |
refine exists_norm_sub_le_mul (admissible_of_isometry hN_adm hf) _, | |
intro m, | |
obtain ⟨_, _, rfl, rfl, n₁, hn₁⟩ := | |
hN _ ⟨hc.out.trans $ le_mul_of_one_le_left' hk'.out⟩ _ (trans hi a.le_succ) (f m), | |
have Hi' : (i - 1) ≤ a + 1 := trans i.pred_le (trans hi a.le_succ), | |
obtain ⟨_, _, rfl, rfl, p₂, hp₂⟩ := hP _ hc _ Hi' (g n₁), | |
rw ← add_zero (_ * ∥_∥) at ⊢, | |
have hn₁₁ : ∥res (f m) - (N.d (i - 1) i) n₁∥ ≤ | |
K * ∥(N.d i (i + 1)) (f m)∥ + 0 / 2 * (1 + K' * r₁ * r₂)⁻¹, rwa [zero_div, zero_mul, add_zero], | |
obtain F := exist_norm_sub_le_mul_norm_add rfl.le hN_adm hgnorm Hg hg hf hc hi hn₁₁ Hi' p₂, | |
by_cases hr : r₂ = 0, | |
{ subst hr, | |
simp at ⊢ F, | |
exact F (trans hp₂ (le_add_of_nonneg_right zero_le_one)) }, | |
{ exact F (by { convert hp₂, simp [hr] } ) } | |
end | |